The chemical oxidation of trichloroethylene (TCE) and tetrachloroethylene (PCE) in contaminated aqueous and soil systems using modified Fenton's chemistry - Go, Jason V. (2003)
Chlorinated solvents indiscriminately disposed to the subsurface impacts not only the soil but may potentially contaminate the groundwater thus impacting the human health as well. Residual contaminants are left in the pores of the soil matrix as the solvent migrate in the subsurface, which in turn may serve as long term source of groundwater contamination. Treatment and removal of these contaminants may be facilitated by chemical oxidation using Fenton's chemistry. Hydroxyl radiclas formed by the action of hydrogen peroxide and the ferrous ion catalyst chemically degrade these organic compounds to relatively benign by products such as carbon dioxide, water and metallic salts.